Departemen Akuntansi Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Mila Sri Utami Hayati; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of Corporate Social Responsibility, environmental accounting, and Environmental Management Systems on environmental performance. The measurement of Corporate Social Responsibility in the environmental field refers to use the Global Reporting Initiative (GRI) score which consists of 26 items to see the level of social responsibility disclosure of the company’s environmental performance.           The population used in this study are mining companies listed on the Indonesia Stock Exchange and listed in the 2015-2019 PROPER assessment. Where the PROPER assessment is a company performance appraisal which is held by the Indonesian Ministry of Environment once a year. The data collection method used in this study was purposive sampling, with companies listed on the Indonesia Stock Exchange and listed on PROPER. Data consisting of 115 data were analyzed. Hypothesis analysis uses descriptive analysis method and multiple linear regression.             The result in this study indicate that Corporate Social Responsibility and Environmental Management System have a significant positive effect on environmental performance. Meanwhile, environmental accounting does not have a significant effect on environmental performance